Job Satisfaction, Organizational Commitment and The Performance-Based Bonus (PBB) System in State Universities and Colleges (SUCS) in Bicol, Philippines - Bongalonta, Michael B.; Bongalonta, Michelle M. (Future Science / FSH-PH Publications, 2022)
This study examined the relationship between job satisfaction and organizational commitment among SUC faculty members and their perception of the PBB system. It also explored the underlying issues in the PBB system and how it could be improved. Mixed design method of research was used. It was found that the faculty members’ perception of the PBB system directly affects their job satisfaction and organizational commitment. Addressing issues in the PBB system becomes urgent given the prevailing wariness and lack of confidence among faculty members towards the way the PBB system is being implemented.